Identifying Public Awareness of the Halal Issue of Cough Medicine Containing Alcohol - Megasari, Gabrilla Ulfa; Widyasti, Lintang Dian; Fahmi, Fahmi (Halal Research, 2024)
This study aimed to identify public awareness regarding the halal status of cough medicines containing alcohol in Indonesia. Although Indonesia is the country with the largest Muslim population, many medicines in Indonesia still contain substances prohibited by Islam, such as alcohol. This research employs a qualitative approach with a literature review to explore the community’s understanding and behavior toward halal-certified medicines. The findings revealed that public awareness regarding the halal status of cough medicines is relatively low. Many respondents did not consistently check for halal logos or ingredients on medicine packaging. Additionally, it is difficult to obtain clear and reliable information about the halal status of these medicines. The study concluded that increased educational and social efforts are necessary to enhance public knowledge and prioritization of halal medicines. Ensuring accessible information on halal certification is crucial for promoting the consumption of halal products, particularly in the health sector.